Study Of Coronary Risk Factors Among Medical Students in Coastal City of Karnataka - Kumar S, Nanjesh; Hameed, Sahul; Alva, Avin BR; Singh, Diwaker Kumar; Kurulkar PV; Jayaram S (National Journal of Community Medicine, 2016)
Background: Cardiovascular disease causes 29 per cent of all deaths globally each year. Lifestyle-related behavioural risk factors are mainly implicated for the increased burden of CHD, and research related to these risk factors among medical students is essential. Objective: To identify coronary risk factors among medical students. Methodology: A cross sectional study was done among M.B.B.S students of a Medical College from November 2012 to March 2014. The study comprised of 500 students. Data was collected by using pre-tested semi structured questionnaire which includes clinical examination and relevant laboratory investigations. Results: Out of 500 subjects 276 were females and 224 were males. 367 (73.4%) subjects were consuming transfattyacid food items. 145 (29%) subjects were overweight and 29 (5.8% ) subjects had Obesity. 76(15.2%) subjects had truncal obesity, 135 (27%) subjects were consuming alcohol and smoking was seen in 58 (11.6%) subjects. 90 (18%) subjects had lack of physical activity, 71 (14.2%) subjects had family history of CHD. 6 (1.2%) subjects had hypertension. Conclusion: Modifiable cardiovascular risk factors are widely prevalent among medical students. Therefore promotion of supportive environment in the medical institutions for strengthening student based approaches and strategic delivery of periodic health education is essential.